2015
DOI: 10.1096/fj.15-278036
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded‐protein response‐associated stabilization of p27(Cdkn1b) interferes with lens fiber cell denucleation, leading to cataract

Abstract: Failure of lens fiber cell denucleation (LFCD) is associated with congenital cataracts, but the pathobiology awaits elucidation. Recent work has suggested that mechanisms that direct the unidirectional process of LFCD are analogous to the cyclic processes associated with mitosis. We found that lens-specific mutations that elicit an unfolded-protein response (UPR) in vivo accumulate p27(Cdkn1b), show cyclin-dependent kinase (Cdk)-1 inhibition, retain their LFC nuclei, and are cataractous. Although a UPR was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 61 publications
2
31
0
Order By: Relevance
“…p27 Kip1 and Cdk1 are important for the disassembly of nuclei envelope and lens DNA degradation (Chaffee et al, 2014; Lyu et al, 2016; Rowan et al, 2016). During fiber cells differentiation the levels of p27 Kip1 protein decreases and becomes undetectable prior to nuclear disassembly.…”
Section: Resultsmentioning
confidence: 99%
“…p27 Kip1 and Cdk1 are important for the disassembly of nuclei envelope and lens DNA degradation (Chaffee et al, 2014; Lyu et al, 2016; Rowan et al, 2016). During fiber cells differentiation the levels of p27 Kip1 protein decreases and becomes undetectable prior to nuclear disassembly.…”
Section: Resultsmentioning
confidence: 99%
“…Three of these models (collagen IV mutant, DN-FGFR, and dnNCOA6) elicit an unfolded protein response (Lyu et al, 2016). We also generated mouse models in which the ubiquitin pathway was perturbed by expression of the ubiquitin variant K6W-Ub (which has lysine 6 replaced by tryptophan).…”
Section: Relationship Between Mitosis and Lfcdmentioning
confidence: 99%
“…Common to each of these models is the activation of endoplasmic reticulum stress due to expression of the transgenes leading to an unfolded protein response (UPR), and associated stabilization of BiP (Fig. 4A)(Lyu et al, 2016). In comparison, expression of K6W-Ub does not show a UPR.…”
Section: Integrated Control Of Cdk1 Activity Via P27 – Role Of Unfmentioning
confidence: 99%
See 1 more Smart Citation
“…Further experiments are required to probe signaling upstream of JNK/mTOR, the phosphorylation of lamin B by Cdk1, and yet to be identified steps in the cascade of cellular and molecular events leading to nuclear degradation in lens fibers (Morishita and Mizushima, 2016). For example, a recent study has revealed a novel role of p27 Kip1 , upstream of Cdk1, in lens fiber cell denucleation (Lyu et al, 2016).…”
Section: Kip2mentioning
confidence: 99%